2018
DOI: 10.1038/s41467-018-07455-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying post-transcriptional regulation in the development of Drosophila melanogaster

Abstract: Even though proteins are produced from mRNA, the correlation between mRNA levels and protein abundances is moderate in most studies, occasionally attributed to complex post-transcriptional regulation. To address this, we generate a paired transcriptome/proteome time course dataset with 14 time points during Drosophila embryogenesis. Despite a limited mRNA-protein correlation (ρ = 0.54), mathematical models describing protein translation and degradation explain 84% of protein time-courses based on the measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 65 publications
(92 reference statements)
5
83
0
Order By: Relevance
“…global transcriptome and proteome analyses prior to and during the MZT have revealed that post-translational regulation of protein stability and function also play a major role in Drosophila (Becker et al, 2018;Casas-Vila et al, 2017;Kronja et al, 2014a) and C. elegans (Stoeckius et al, 2014). For example, in C. elegans more than one-quarter of the transcriptome is downregulated at least twofold in early embryos, whereas only 5% of the proteome shows a similar decrease (Stoeckius et al, 2014).…”
Section: Post-translational Regulation Of Maternal Proteinsmentioning
confidence: 99%
“…global transcriptome and proteome analyses prior to and during the MZT have revealed that post-translational regulation of protein stability and function also play a major role in Drosophila (Becker et al, 2018;Casas-Vila et al, 2017;Kronja et al, 2014a) and C. elegans (Stoeckius et al, 2014). For example, in C. elegans more than one-quarter of the transcriptome is downregulated at least twofold in early embryos, whereas only 5% of the proteome shows a similar decrease (Stoeckius et al, 2014).…”
Section: Post-translational Regulation Of Maternal Proteinsmentioning
confidence: 99%
“…and transcriptome excluded almost all proteins in Cluster 6 from their analysis because of these 171 proteins' narrow expression window (Becker et al, 2018). 172…”
Section: Dynamics Of the Proteome Relative To The Transcriptome And Tmentioning
confidence: 99%
“…While this central dogma has been established over the last 60 years, the non-linearity between the levels of a given mRNA and the amount of protein it encodes has only recently started to emerge (5)(6)(7)(8). One explanation for this poor correlation resides in the spatial control of translation that could lead to differential protein output.…”
Section: Introductionmentioning
confidence: 99%